БОЛАЛАРДА ХУЛҚ-АТВОР БУЗИЛИШЛАРИНИ КОРРЕКЦИЯ ҚИЛИШ ТЕХНОЛОГИЯЛАРИ ВА УЛАРНИНГ САМАРАДОРЛИГИ - Бахронова, К.Я. (SCIENCE and SOCIETY, 2025)
This article analyzes behavioral disorder correction technologies and their effectiveness. In particular, it examines the cognitive restructuring method, which is one of the key tools of cognitive-behavioral therapy (CBT). This method is aimed at identifying irrational thoughts and transforming them into constructive beliefs, thereby improving personal and social adaptation. The article explores correctional approaches to behavioral disorders such as depression, anxiety, aggression, social phobia, and stress-related issues, as well as analyzes the practical application and outcomes of the cognitive restructuring method. The effectiveness of correction technologies is presented in percentage indicators based on scientific research and experimental data.
Keywords: cognitive restructuring; cognitive-behavioral therapy; behavioral disorders; psychological correction; stress management; psychotherapy; cognitive approach